2005
DOI: 10.3928/1542-8877-20050501-07
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Pars Plana Vitrectomy Combined With Filtering Surgery for Neovascular Glaucoma

Abstract: * BACKGROUND AND OBJECTIVE: To analyze the effectiveness of vitrectomy combined with filtering surgery for neovascular glaucoma. * PATIENTS AND METHODS: Twenty-one eyes with neovascular glaucoma underwent pars plana vitrectomy combined with filtering surgery between January 1995 and December 2003. Thirteen eyes (10 cases) had neovascular glaucoma secondary to proliferative diabetic retinopathy and 8 eyes (8 cases) had neovascular glaucoma secondary to central retinal vein occlusion. The initial intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Bartz-Schmidt et al [1], who reduced the IOP by cyclophotocoagulation, reported 10 of 32 eyes (31.3%) lost light perception. On the other hand, the pars plana filtration method used by Kono et al [6] led to a loss of light perception in only two of 21 eyes (9.5%). Their procedure appeared safe, but they did not mention the severity of complications associated with filtration at the pars plana.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Bartz-Schmidt et al [1], who reduced the IOP by cyclophotocoagulation, reported 10 of 32 eyes (31.3%) lost light perception. On the other hand, the pars plana filtration method used by Kono et al [6] led to a loss of light perception in only two of 21 eyes (9.5%). Their procedure appeared safe, but they did not mention the severity of complications associated with filtration at the pars plana.…”
Section: Discussionmentioning
confidence: 97%
“…Their success rate of maintaining an IOP ≤21 mmHg with preservation of light perception was 56% after 1 year. Kono et al [6] reported on the effect of pars plana vitrectomy combined with filtering surgery for NVG. Their filtering surgery consisted of making microholes at the pars plana by irradiating with the endolaser after resecting the sclera.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As surgical instrumentation and skills have improved, more complicated cases are being operated on[ 61 ] and the threshold for surgery has decreased. [ 42 43 62 63 64 65 66 ] Advances in vitreoretinal surgery include wide-field viewing systems, multiport illumination systems,[ 67 ] perfluorocarbon liquids, and silicone oil. [ 45 ] The use of silicone oil, as opposed to long-acting gas tamponade, may accelerate visual rehabilitation, maintain tamponade, prevent hypotony,[ 68 ] and decrease the incidence of recurrent bleeding or rubeosis.…”
Section: Managementmentioning
confidence: 99%